1987
DOI: 10.1002/sia.740100803
|View full text |Cite
|
Sign up to set email alerts
|

SIMS and XPS studies of polyurethane surfaces 2. Polyurethanes with fluorinated chain extenders

Abstract: A series of fluorine-containing segmented poly(ether urethanes) and poly(ether urethane ureas), previously characterized by angular dependent x-ray photoelectron spectroscopy (XPS) have been re-examined using static secondary ion mass spectrometry (SIMS). Comparison of the data from the two techniques has shown that the intensity of secondary ion signals which characterize the hard and soft segments can be used quantitatively for direct analyis of the molecular cymposition at the surface. Moreover, the SIMS sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(42 citation statements)
references
References 19 publications
4
38
0
Order By: Relevance
“…Numerous experimental techniques including Fourier transform infrared (FTIR) spectroscopy [5,6], near-infrared (NIR) spectroscopy [7,8], differential scanning calorimetry (DSC) [5,[9][10][11], dynamic mechanical analysis (DMA) [12,13], transmission electron microscopy (TEM) [14,15], X-ray photoelectron spectroscopy (XPS) [5,[16][17][18], and many others have been used to analyze phase separation in polyurethanes.…”
Section: Reinforcementmentioning
confidence: 99%
“…Numerous experimental techniques including Fourier transform infrared (FTIR) spectroscopy [5,6], near-infrared (NIR) spectroscopy [7,8], differential scanning calorimetry (DSC) [5,[9][10][11], dynamic mechanical analysis (DMA) [12,13], transmission electron microscopy (TEM) [14,15], X-ray photoelectron spectroscopy (XPS) [5,[16][17][18], and many others have been used to analyze phase separation in polyurethanes.…”
Section: Reinforcementmentioning
confidence: 99%
“…Angle-dependent XPS and static secondary ion mass spectroscopy (SSIMS) analysis of this PEU indicated that the surface was enriched with the ether segments of the polymer. 21 The sample was centrifugally cast onto glass coverslips from a 20 mg ml-I solution in DMAC. The glass coverslips were cleaned prior to polymer casting, following the procedure suggested by Ratner et a1."…”
Section: Samplesmentioning
confidence: 99%
“…15,16 Static SIMS is much more surface sensitive than XPS and, because of its basis in mass spectrometry, more chemically selective too. The extremely high analytical sensitivity of static SIMS, the sampling depth of 10-15Å for polymers 17 and molecular information about both protein film chemistry and substrate chemistry offer the potential to gain a detailed understanding of the composition, structure, conformation and orientation of adsorbed protein films. Previously we have refined our abilities to interpret the static SIMS spectra of proteins, allowing individual amino acids to be monitored unambiguously.…”
Section: Introductionmentioning
confidence: 99%